2013
DOI: 10.1017/s1352465813000714
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation into the Existence of a Hypervigilance Subtype of Auditory Hallucination in People with Psychosis

Abstract: The results offered tentative support for the existence of an HV-AH subcategorization and justifies future research in larger samples. Potential implications for models of AHs are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
(38 reference statements)
3
20
0
1
Order By: Relevance
“…52 This study also found evidence for another AVH subtype, characterized as occurring in a quiet environment when voice hearers’ attention was internally focused. These AVH could contrastingly be conceived of as having their basis in memories or misattributed inner speech, raising the possibility of subtyping at this level.…”
Section: Subtyping By Cognitive Processessupporting
confidence: 61%
“…52 This study also found evidence for another AVH subtype, characterized as occurring in a quiet environment when voice hearers’ attention was internally focused. These AVH could contrastingly be conceived of as having their basis in memories or misattributed inner speech, raising the possibility of subtyping at this level.…”
Section: Subtyping By Cognitive Processessupporting
confidence: 61%
“…In relation to hyperarousal, a hypervigilance subtype of voice hearing has been previously proposed (McCarthy-Jones et al, 2012, 2014; Garwood et al, 2015) and within this model is viewed as linked to the sensitization of the sympathetic nervous system following childhood victimization. Understandable hypervigilance to danger may result in a reduced threshold for threat detection in environmental noise (e.g., perceiving background sounds of people talking or traffic as a sign of danger), leading to intrusions of anomalous experiences.…”
Section: A Model Of Posttraumatic Stress In Psychosismentioning
confidence: 99%
“…The aim was to lay bare the essence of an experience and make it intelligible to others. In light of this first‐person orientation, phenomenology can be viewed as the foundational science for psychopathology , yet relatively few papers publish primary evidence on the phenomenology of AVH experience (See Table S1).…”
Section: Phenomenological Enquirymentioning
confidence: 99%